Investigation of cure kinetics in epoxy/multiwalled carbon nanotube nanocomposites - Susin S.B. (2014)
With the increased interest in thermoset resin nanocomposites, it is important to understand the effects of the material on nanoscale characteristics. In this study, a curing reaction of an epoxy resin, which contained 0.25, 0.50, or 1.00 wt % of multiwalled carbon nanotubes (MWCNTs), at different heating rates was monitored by differential scanning calorimetry; cure kinetics were also evaluated to establish a relationship between crosslinking (network formation) and mechanical properties. MWCNT concentrations above 0.25 wt % favored crosslinking formation and decreased the activation energy (E a) in the curing reaction. Examination of the kinetic mechanism suggests that the MWCNT locally restricted the spatial volume and favored the formation of nodular morphology in the resin, especially for high MWCNT concentrations. The MWCNT exhibited some entanglement in the matrix, which hindered a more pronounced effect on the mechanical properties. © 2013 Wiley Periodicals, Inc.